Granulosa cell tumor in Arabian mares: prevalence, risk factors, clinical and histopathological findings and outcome of surgical removal - Derar, Derar; Ali, Ahmed; Al-Sobayil, Fahd; Refaai, Walid (Frontiers in Veterinary Science, 2025)
IntroductionGranulosa cell tumors (GCTs) represent the most common ovarian neoplasms in mares, yet data on their epidemiology, risk factors, and clinical outcomes in Arabian horses are limited. Understanding their prevalence and diagnostic features is crucial for improving fertility management in this breed.MethodsClinical records from 807 Arabian mares housed on 35 stud farms in central Saudi Arabia were retrospectively reviewed to determine the prevalence of GCT and potential risk factors, including age, parity, and anabolic steroid use. Twenty-four confirmed cases were further investigated using clinical examination, ultrasonography, endocrine profiling, and histopathology. Surgical management by unilateral ovariectomy was performed in 20 mares, and postoperative fertility outcomes were documented.ResultsThe overall prevalence of GCT was 0.6%. Logistic regression analysis identified anabolic steroid use as a significant risk factor (Odds Ratio = 13.21, p = 0.0001). Stallion-like behavior was the most frequent clinical manifestation (58.3%), followed by anestrus (33.3%) and persistent estrus (8.3%). Ultrasonography revealed four distinct tumor morphologies, with contralateral ovarian atrophy present in 75% of cases. Histopathology classified tumors into adult type (76.5%) and juvenile type (23.5%). Preoperative testosterone concentrations were elevated and decreased postoperatively in 72.7% of mares. Ovariectomy resulted in an 80% recovery rate, with 68.8% of mares regaining fertility.DiscussionThis study demonstrates that anabolic steroid administration markedly increases the risk of GCT in Arabian mares. Behavioral changes, ultrasonographic appearance, and hormonal profiles remain key diagnostic indicators, while histopathology confirms tumor classification. Surgical excision proved effective, with favorable fertility outcomes in most mares. These findings underscore the importance of early diagnosis and highlight the need for judicious use of anabolic steroids in breeding programs.